Vozrastnye osobennosti fizicheskoi podgotovlennosti lyzhnits-gonshchits - Golovachev, A. I. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The problem of this article concerned around the expanding of functional abilities of main energy supplying systems. During the research authors inquired the marks of physical preparedness for each age group of athletes, and analyzed them. Then they defined the most significant marks for each group. Authors concluded, that the most significant mark for all groups is the mark of maximal oxygen consuming (MOC). In addition to that the marks of MOC per kilo of weight and the coefficient of oxygen consuming at the threshholding level are noted also for different groups.